Analisis Kerjasama UPT Perpustakaan Proklamator Bung Hatta Kota Bukittinggi Dengan Lembaga Informasi - Afrina, Cut -; Syafrinal S, Syafrinal S; Annisa, Annisa; Ariyanti, Annisa; Aulia Rahma, Arini; Nazira, Hanifa; Yuli Yanti, Fivi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research uses descriptive qualitative methods with a field research approach. This study aims to examine the phenomenon of institutional cooperation in the information field at the Hatta Proclamation Library in Bukittinggi City. The research methods used were direct interviews with related parties and primary data collection. The results of this study will provide a detailed picture of the collaboration carried out by UPT Proclamation Library Hatta with information institutions. Based on this research, it can be concluded that institutional cooperation in the field of information at the Hatta Proclamation Library in Bukittinggi City has been carried out through collaboration with other information institutions. This collaboration is carried out with the aim of helping others and achieving specified goals. Descriptive qualitative research methods are used to examine this phenomenon of cooperation holistically and describe the characteristics of the activities carried out. The results of this study are expected to provide a deeper understanding of institutional cooperation in the field of information.